Tailored SMS messages to consumers for improving nutrition - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
Tested under GAIN - mainly nutrition but some food safety. Delivered at scale in several countries. Weak evaluations were moderately positive. No business model could be developed. but further delivery halted because funding not available.